Exertional-heat stress-associated gastrointestinal perturbations during Olympic sports: Management strategies for athletes preparing and competing in the 2020 Tokyo - Costa, R. J. S.; Gaskell, S. K.; McCubbin, A. J.; Snipe, R. M. J. (Temperature, 2020)
Exercise-induced gastrointestinal syndrome (EIGS) is a common characteristic of exercise. The causes appear to be multifactorial in origin, but stem primarily from splanchnic hypoperfusion and increased sympathetic drive. These primary causes can lead to secondary outcomes that include increased intestinal epithelial injury and gastrointestinal hyperpermeability, systemic endotoxemia, and responsive cytokinemia, and impaired gastrointestinal function (i.e. transit, digestion, and absorption). Impaired gastrointestinal integrity and functional responses may predispose individuals, engaged in strenuous exercise, to gastrointestinal symptoms (GIS), and health complications of clinical significance, both of which may have exercise performance implications. There is a growing body of evidence indicating heat exposure during exercise (i.e. exertional-heat stress) can substantially exacerbate these gastrointestinal perturbations, proportionally to the magnitude of exertional-heat stress, which is of major concern for athletes preparing for and competing in the upcoming 2020 Tokyo Olympic Games. To date, various hydration and nutritional strategies have been explored to prevent or ameliorate exertional-heat stress associated gastrointestinal perturbations. The aims of the current review are to comprehensively explore the impact of exertional-heat stress on markers of EIGS, examine the evidence for the prevention and (or) management of EIGS in relation to exertional-heat stress, and establish best-practice nutritional recommendations for counteracting EIGS and associated GIS in athletes preparing for and competing in Tokyo 2020.